Remarks at the Second World Water Forum: From Vision to Action - Wolfensohn, James D. (World Bank, Washington, DC, 2019)
James D. Wolfensohn, President of the World Bank Group, noted that in many parts of the world, access to water distinguishes the poor from the non-poor. Lack of access to water is synonymous with poverty throughout the developing world. In Cote d'Ivoire and Benin more than 70 percent of people now have access to safe water. The Bank must look at the institutions to see how one can give stakeholders a real stake, how one can use water more efficiently, and how one can make service providers more accountable. He discussed technological and financial innovation and the challenge of inclusion. The Bank’s overarching goal remains to bring together all the elements that will enable to eradicate the human, social, and economic degradation of poverty; all the elements that will help to build a peaceful and secure world for future generations; all the elements that promise people healthier and more prosperous lives.